Jewish themes in the New Testament : Am Yisrael Chai! - Morris, Paul, 1948- (Paternoster, 2013)
Jewish Themes in the New Testament is an examination of what the New Testament teaches about the Jewish people in the era of the New Covenant. The core of that teaching is an affirmation of God's continued faithfulness to them. In a day when opinions regarding the Jewish people are increasingly polarised as some stress their position centre-stage and others consign them to the dustbin of history, this book seeks to demonstrate from the New Testament that both extremes are wrong. This unique book considers the theological issues, but it is concerned for much more; it is about Jewish people and the Jews as a people, as the New Testament sees them.